Students? Perceptions of the Impact of Blended Learning on Their Learning Experience - Jamaluddin J.E.; Anuar A.; Ibrahim Z. (Springer Science and Business Media Deutschland GmbH, 2025)
This paper presents a study on the perception and effectiveness of the blended learning (BL) approach at Universiti Tenaga Nasional (UNITEN). The study aimed to evaluate whether BL aids students? understanding of course material, enhances enjoyment in learning, and contributes to better grades. Data from 533 students across five colleges at UNITEN were collected using an online survey with Likert scale questions. Analysis of the responses showed a generally positive perception of BL across all areas, with slight variations across different colleges. Students from the College of Business Management and Accounting perceived the highest benefits in terms of understanding, enjoyment, and grades, while students from the College of Engineering and College of Computing and Informatics indicated a lesser impact of BL on their grades. These findings suggest that while BL is generally beneficial, its implementation and impact may vary across different academic disciplines, warranting further tailored refinements. The study contributes to understanding the students? perspective on BL and offers insights for its effective implementation across diverse disciplines. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.